2021
DOI: 10.1097/tp.0000000000003247
|View full text |Cite
|
Sign up to set email alerts
|

CD38 Antibody Daratumumab for the Treatment of Chronic Active Antibody-mediated Kidney Allograft Rejection

Abstract: Background. Late antibody-mediated rejection (AMR) is a major cause of transplant failure. Potential therapeutic targets are plasma cells and natural killer (NK) cells, both expressing high levels of CD38. Methods. Here, we report the use of CD38 monoclonal antibody daratumumab (9-mo course) in a kidney allograft recipient diagnosed with smoldering myeloma and anti-HLA class II donor-specific antibody-positive chronic active AMR 13 years after transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…In the last decade, several strategies to handle with autoimmune or alloimmune pathologic situations include CD38 antibodies (71)(72)(73).…”
Section: Cd38 Antibodies In Solid Organ Transplantation Cd38 Antibodies In Non Tumoral Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, several strategies to handle with autoimmune or alloimmune pathologic situations include CD38 antibodies (71)(72)(73).…”
Section: Cd38 Antibodies In Solid Organ Transplantation Cd38 Antibodies In Non Tumoral Contextmentioning
confidence: 99%
“…A recurrent acute PC-rich rejection on kidney biopsy and significant ascension of DSA were successfully managed with daratumumab. Recently, two others cases were reported: one refractory ABMR after a heart transplant successfully treated with daratumumab and one chronic active ABMR in a kidney allograft recipient diagnosed with myeloma exposed to daratumumab (73,86). In the last one, the exhaustive immuno-monitoring showed that the main mode of action seems to be based on PC depletion, with profound PCs reduction in the bone marrow and peripheral blood and the abrogation of in vitro alloantibody production by PC enriched from bone marrow aspirates, leading to significant reduction in DSA levels (73).…”
Section: Cd38 Antibodies and Abmr Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope that this antibody, possibly in combination with other therapeutic options, can improve treatment of ABMR in the near future. 13,14 All in all, the strategies to improve long-term outcomes of kidney transplantation are manifold and also go beyond clinical interventions. 15 Based on the tremendous improvements in kidney transplantation care over the last decades, it is fair to believe that we as transplant community will find ways to further enhance the survival of our kidney transplant patients in the future.…”
Section: Future Directions Of Research and Carementioning
confidence: 99%
“…Daratumumab, an antibody directed against the B‐cell antigen CD38, was reported to have stopped ABMR in a patient receiving it for the treatment of multiple myeloma. We hope that this antibody, possibly in combination with other therapeutic options, can improve treatment of ABMR in the near future 13,14 …”
Section: Future Directions Of Research and Carementioning
confidence: 99%